PENGUKURAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KELOR (Moringa oleifera Lam.) MENGGUNAKAN METODE FRAP (Ferric Reducing Antioxidant Power) - St Maryam; Muzakkir Baits; Ainun Nadia (Jurnal Fitofarmaka Indonesia, 2015)
Measurement of antioxidant activity of ethanol extract of Marunggai leaves (Moringa oleifera Lam) was conducted. The aim research to obtain antioxidant activity using FRAP (Ferric Reducing Antioxidant Power). Marunggai leaves (Moringa oleifera Lam.) ware extracted using maceration method by ethanol 96 %. Free radical activity absorbance was measured with a spectrophotometer at a wavelength of 720 nm and the total value of antioxidant activity was calculated based on the data absorbance. The calculations showed that Marunggai leaves (Moringa oleifera Lam.) have the antioxidant activity with the value 7,923 mg AAE/g extract.